2002
DOI: 10.2172/797857
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution of eutectic Au-Sn solder joints

Abstract: Current trends toward miniaturization and the use of lead(Pb)-free solders in electronic packaging present new problems in the reliability of solder joints. This study was performed in order to understand the microstructure and microstructural evolution of small volumes of nominally eutectic Au-Sn solder joints (80Au-20Sn by weight), which gives insight into properties and reliability. The study particularly concentrated on the effects that the joint size and the type of substrate metallization have on both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The solder material and gold/tin-tonickel interface remained undamaged. In [6], it was found that eutectic gold/tin bumps on an electroless nickel UBM yielded a (Ni, Au) 3 Sn 2 intermetallic layer with an average thickness of 0.7 µm for reflow temperatures similar to temperatures used in this work. According to [6], this intermetallic allows for good adhesion and large fracture strength between the eutectic gold/tin and the nickel layer.…”
Section: Gold/tin Solderingmentioning
confidence: 56%
See 1 more Smart Citation
“…The solder material and gold/tin-tonickel interface remained undamaged. In [6], it was found that eutectic gold/tin bumps on an electroless nickel UBM yielded a (Ni, Au) 3 Sn 2 intermetallic layer with an average thickness of 0.7 µm for reflow temperatures similar to temperatures used in this work. According to [6], this intermetallic allows for good adhesion and large fracture strength between the eutectic gold/tin and the nickel layer.…”
Section: Gold/tin Solderingmentioning
confidence: 56%
“…Before thinning, the test chips were prepared for Daisy chains and Kelvin contact measurements by electroplating of gold wires and two-layered Au/Sn bumps. Gold/tin interconnects are known for their superior properties, as for example low creep, large fracture strength, a eutectic melting temperature of 280 • C (for the eutectic composition Au80Sn20), low resistivity, large corrosion resistance and biocompatibility [5][6][7]. To minimize spreading of the tin along the gold wires, a 2 µm nickel diffusion barrier was also electroplated before the gold/tin layers.…”
Section: Gold/tin Solderingmentioning
confidence: 99%